The dynamic behavior and mechanism of uranium (VI) biomineralization in Enterobacter sp. X57. (July 2022) - Zeng, Qian; Zhu, Ting; Wen, Yufeng; Li, Feize; Cheng, Yanxia; Chen, Shunzhang; Lan, Tu; Yang, Yuanyou; Liao, Jiali; Sun, Qun; Liu, Ning
Abstract: The important role of microbes in the biomineralization and migration behavior of uranium in the field of environmental chemistry has been well emphasized in previous work. However, limited work on mineralization processes of indigenous microorganism has prevented us from a deeper understanding of the process and mechanisms of uranium biomineralization. In this work, the dynamic process and mechanism of uranium biomineralization in Enterobacter sp. X57, a novel uranium-tolerant microorganism separated from uranium contaminated soil, were systematically investigated. Enterobacter sp. X57 can induce intracellular mineralization of U (VI) to Uramphite (NH4 UO2 PO4 ·3H2 O) under neutral conditions by alkaline phosphatase. In this biomineralization process, soluble U (VI) first bonded with the amino and phosphate groups on the plasma membrane, providing initial nucleation site for the formation of U (VI) biominerals. Then the impairment of cell barrier function and the enhancement of alkaline phosphatase metabolism occurred with the accumulation of uranium in cells, creating a possible pathway for soluble U (VI) to diffuse into the cell and be further mineralized into U (VI)-phosphate minerals. All the results revealed that the intracellular biomineralization of uranium by Enterobacter sp. X57 was a combined result of biosorption, intracellular accumulation and phosphatase metabolism. These findings may contribute to a better understanding of uranium biomineralization behavior and mechanism of microorganisms, as well as possible in-situ bioremediation strategies for uranium by indigenous microorganisms. Graphical abstract: Image 1 Highlights: The dynamic process of U-mineralization by Enterobacter sp. X5 7 has been revealed. Toxic soluble U (Ⅵ) could vitiate the cell wall and diffuse into the cell gradually. Intracellular U (Ⅵ) converted into insoluble U mineral along the plasma membrane. U-biomineralization in Enterobacter sp. X57 was promoted by alkaline phosphatase.